On the Limitations of the Implicit Morality of the Market: A Perspective from Modern Economic Analysis - Stefano Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
The paper explores the norms and values supporting the market as a social institution,seeking to outline them explicitly. After this, it addresses the following questions: what dimensions of value in things, relationships and persons are acknowledged or ignored by the norms of the market? Second, what are the ideals of self and society that the market attempts to embody? Third, does the extension of the market to a certain realm undermine the realization of other ideals? The main point of the paper is that market forces must embedded in supportive, but constraining, social, institutional and normative frameworks.
Keywords: 330